Anti-thermal behavior of materials. (1st July 2015) - Cantwell, Patrick R.; Holm, Elizabeth A.; Harmer, Martin P.; Hoffmann, Michael J.
Abstract: Thermally activated processes such as diffusivity, grain growth, oxidation, and catalysis are often modeled using the Arrhenius equation, in which the steady-state process rate increases with increasing temperature, yielding a positive activation energy. However, in some systems, the process rate is constant or decreases with increasing temperature. Mechanistic explanations for many types of anti-thermal behavior are lacking. By learning how to control anti-thermal behavior, major advances are possible in fields ranging from catalysis to nanocrystalline alloys to high efficiency engines.